Vibrational spectra of hydrogenated and halogenated graphene CX; X=H, F, Cl - Sharma, Sandeep Kumar; Singh, Ranber; Kühne, Thomas D. (Materials Research Express, 2019)
In this paper, we investigate the Raman and infra-red (IR) spectra of fully hydrogenated and halogenated graphene in a chair, boat and washboard conformations. The IR spectra of chair conformations have two peaks due to Eu and A2u phonons,while their Raman spectra have four peaks due to Eg and A1g phonons. There are lowand high frequency in-plane Eg phonons and out-of-plane A1g phonons which give rise to four peaks in the Raman spectra. The optimized structures of the boat and washboard conformations ofCHhave different point group symmetries. The optical phonons of these conformations ofCHare either IR active or Raman active. However, the optimized structures of the boat and washboard conformations o fCF and CCl are a bit twisted and have the same C2v(mm2) point group symmetries. In these conformations, there are four Raman active A2 phonons and several otherA1, B1 and B2 phonons which are both Raman and IR active.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Graphene; Infra red spectra; Raman spectra